Detecting Fraudulent Financial Reporting Through Hexagon Fraud Model: Moderating Role of Income Tax Rate - Meidijati, Meidijati; Amin, Muhammad Nuryatno Amin (International Journal of Social and Management Studies, 2022)
Researchers analyze to collect empirical evidence to test the effect of independent variables of the hexagon fraud model, namely stimulus (STM), capability (CPB), collusion (CLL), opportunity (OPP), rationalization (RZN), and ego (EGO), on the variable dependent, namely detection of fraudulent financial reporting (FFR), with the income tax rate as a moderating variable. One of the motivations of a company or person to commit FFR is related to tax motives. The research uses the hexagon fraud (Vousinas, 2019) and there are indicators related to taxes are book-tax differences (BTD) to measure financial targets in STM variable and income tax rate (ITR) to measure the role of moderating variable. The sample data of this research are 480 public companies in Indonesia engaged in manufacturing in 2015 to 2019. Research results reveal that STM, RZN, and EGO have a positive effect on FFR, CPB and OPP have a negative effect on FFR. ITR strengthens the effect of CPB on FFR, and ITR weakens the effect of EGO on FFR. The research findings support the hexagon theory of fraud. This research can explain the phenomenon of fraudulent financial reporting and can be beneficial to regulators, management, and various stakeholders in detecting FFR.